1995
DOI: 10.1021/bi00014a033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human and Rat Intestinal Trefoil Factor Produced in Yeast

Abstract: Intestinal trefoil factor (ITF) from human (hITF) and rat (rITF) have been produced in Saccharomyces cerevisiae. The DNA encoding the two peptides were cloned by polymerase chain reactions (PCR) from a human normal colon library and a rat small intestinal epithelial cell library. Recombinant plasmids were constructed to encode a fusion protein consisting of a hybrid leader sequence and the rat and human ITF sequences, respectively. The leader sequence used serves to direct the fusion protein into the secretory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 39 publications
10
76
0
Order By: Relevance
“…When required, the CXCR4 antagonist AMD3100 (Sigma) was added into luminal perfusate (10 M) as well as given subcutaneously (5 mg/kg in saline, 1 h prior to experiments). In some experiments, the rat trefoil factor 3 peptide (rTFF3, 2 mg/ml in saline, solubilized on the day of the experiment) was topically applied to the exposed gastric surface at two to three times within 20 min (29). We are very grateful to Dr. Daniel Podolsky for supplying the rTFF3 peptide.…”
Section: Methodsmentioning
confidence: 99%
“…When required, the CXCR4 antagonist AMD3100 (Sigma) was added into luminal perfusate (10 M) as well as given subcutaneously (5 mg/kg in saline, 1 h prior to experiments). In some experiments, the rat trefoil factor 3 peptide (rTFF3, 2 mg/ml in saline, solubilized on the day of the experiment) was topically applied to the exposed gastric surface at two to three times within 20 min (29). We are very grateful to Dr. Daniel Podolsky for supplying the rTFF3 peptide.…”
Section: Methodsmentioning
confidence: 99%
“…In some experiments, T84 cells were grown on inserts of 0.4 mm pore size (Falcon 3090; BD Biosciences, Mountain View, CA), and used after achieving transepithelial resistance Ͼ400⍀ determined with a Millicell-ERS (Millipore, Bedford, MA) apparatus. Purified recombinant human ITF was produced as described previously (28).…”
Section: Cells and Recombinant Itfmentioning
confidence: 99%
“…4 The distinct threelooped secondary structure contributes to the remarkable resistance of trefoil factors to acid and proteolytic digestion, enables them to function in the harsh environment of the gastrointestinal tract lumen, and allows them to remain biologically active after enteral administration. 5,6 We have previously demonstrated that significant amounts of TFF3/ITF are present in the meconium of human infants at different gestational ages. 7 However, whether secreted TFF3/ITF in the human meconium is biologically active remains to be tested.…”
mentioning
confidence: 99%